2020
DOI: 10.1111/ene.14563
|View full text |Cite
|
Sign up to set email alerts
|

Corneal sub‐basal whorl‐like nerve plexus: a landmark for early and follow‐up evaluation in transthyretin familial amyloid polyneuropathy

Abstract: Background and purposeSmall‐fiber nerves are the first to be involved in transthyretin familial amyloid polyneuropathy (TTR‐FAP) patients. In vivo corneal confocal microscopy (CCM) is a noninvasive technique to detect small‐fiber polyneuropathy (SFN) by quantifying corneal nerve morphology. The characteristic whorl‐like pattern of the corneal nerve provides a static landmark for observation. We aimed to evaluate whether CCM images of the whorl‐like plexus can sensitively evaluate and monitor disease progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
1
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 43 publications
(55 reference statements)
3
21
1
1
Order By: Relevance
“…Comparison of corneal nerve length at the more distal inferior whorl with more proximal central corneal nerves enables an assessment for a dying-back neuropathy. Zhang et al showed that a reduction in inferior whorl length occurred in in patients with sub-clinical familial amyloid polyneuropathy [8]. In a cross-sectional study, we have previously reported greater corneal nerve loss at the IW compared to the central cornea in patients with diabetic neuropathy [9], and there was greater corneal nerve loss at the IW compared to the central cornea in a longitudinal study [10].…”
Section: Introductionmentioning
confidence: 73%
“…Comparison of corneal nerve length at the more distal inferior whorl with more proximal central corneal nerves enables an assessment for a dying-back neuropathy. Zhang et al showed that a reduction in inferior whorl length occurred in in patients with sub-clinical familial amyloid polyneuropathy [8]. In a cross-sectional study, we have previously reported greater corneal nerve loss at the IW compared to the central cornea in patients with diabetic neuropathy [9], and there was greater corneal nerve loss at the IW compared to the central cornea in a longitudinal study [10].…”
Section: Introductionmentioning
confidence: 73%
“…This lack of a floor effect increases the utility of CNFL compared to IENFD in longitudinal and interventional studies of amyloid neuropathy. Recently, a study from China has confirmed and extended these findings by showing corneal nerve loss in the central and inferior whorl regions with an AUC for CNFL and IWL of 88.0 and 89.3%, respectively, for the diagnosis of familial amyloid neuropathy ( 57 ).…”
Section: Ccm In Peripheral Neuropathiesmentioning
confidence: 83%
“…The fatal inherited disorder, transthyretin familial amyloid polyneuropathy, is characterized by a progressive neuropathy and cardiomyopathy [ 57 ]; CNFL is reduced in patients with this condition [ 58 ] and has good diagnostic utility [ 59 ].…”
Section: Ccm In Other Peripheral Neuropathiesmentioning
confidence: 99%